Restructuring Charges and CEO Cash Compensation: A Reexamination - Adut, Davit; Cready, William H.; Lopez, Thomas J. (The Accounting Review, 2003)
Prior research generally concludes that compensation committees completely shield executive compensation from the effect of restructuring charges on earnings. In contrast, we find that after controlling for the growth in annual inflation-adjusted CEO cash compensation, compensation committees only partially shield CEO compensation from the adverse effect of restructuring charges on earnings, on average. In further analyses, we identify factors associated with cross-sectional differences in the extent of shielding. Specifically, we find that compensation committees appear to: (1) completely shield initial and subsequent restructuring charges for CEOs with long tenure, provided that the firm had not recorded a charge in the two immediately prior years; (2) provide no shielding of subsequent restructuring charges taken by short-tenured CEOs if the firm reported a prior restructuring charge within two years of the current charge; (3) and partially shield the other categories of restructuring charges. Overall, this study provides evidence that compensation committees evaluate the context of each restructuring in determining the extent to which they will intervene to shield executive compensation from the effect of these charges.